Dissociating rehearsal and refreshing in the maintenance of verbal information in 8-year-old children - Mora, Gérome; Camos, Valérie (Frontiers in Psychology, 2015)
Recent models of working memory suggest that two systems are involved in verbal working memory: one is dedicated to the maintenance of phonological representations through verbal rehearsal, while the other would maintain multimodal representations through attentional refreshing (Baddeley, 2012; Camos et al., 2009). Previous studies provided evidence on the existence of these two maintenance systems, on their independence, and how they affect recall performance in adults. However, only one study had already explored the relationships between these two systems in children (Tam et al., 2010). The aim of the present study was to further examine how the two systems account for working memory performance in children. Eight-year-old children performed complex span tasks in which the availability of either the rehearsal or the refreshing was impeded by a concurrent articulation or an attention-demanding task, respectively. Moreover, the phonological similarity of the memoranda was manipulated. Congruently with studies showing that older children can used these maintenance systems, impeding any of the two systems reduced recall performance. Moreover, the manipulation of the two mechanisms did not interact, as previously observed in adults. This suggests that the two maintenance mechanisms are independent in 8-year-old children as they are in adults. However, the results concerning the phonological similarity effect differed from what is observed in adults. Whereas the phonological similarity effect relies only on the availability of rehearsal in adults, a more complex pattern appeared in children: the concurrent articulation as well as the concurrent task modulated the emergence of the phonological similarity effect.